Pricing participating longevity-linked life annuities - Bravo, Jorge Miguel (2022)
Bravo, J. M. (2022). Pricing participating longevity-linked life annuities: a Bayesian Model Ensemble approach. European Actuarial Journal, 12(1), 125-159. https://doi.org/10.1007/s13385-021-00279-w ------ The author would like to express his gratitude to the editor and to two anonymous referees for his or her careful review and insightful comments, that helped strengthen the quality of the paper. We thank also the suggestions and remarks from participants at the CAPSI 2020 Conference, Porto. The author was supported by Portuguese national science funds through FCT under the project UIDB/04152/2020-Centro de Investigação em Gestão de Informação (MagIC).